The Apparent Decline in Capital-Output Ratios - Anderson, Paul S. (Quarterly Journal of Economics, 1961)
I. Goldsmith and MAPI ratios, 615. — II. Rise and fall in manufacturing ratios, 618. — III. Railroads, 622. — IV. Implications of the savings ratio, 625. — V. Summary, 629.